Inelastic processes in ion interaction with ZrO2 surface. (July 2016) - Khvostov, V.V.; Zykova, E.Yu.
Abstract: Experimental studies and computer simulations of inelastic interaction of low-energy Ar + ions (100–2000 eV) with a ZrO2 surface are presented. The experiments were performed using Auger electron spectroscopy and secondary ion mass spectrometry. It has been found that the change of surface composition and the intensities of sputtered Zr + and scattered Ar + ions depend non-monotonically on the incident ion energy. Moreover, Zr + and Ar + ion intensities oscillate in antiphase and correlate with the curve of the surface composition change. The results of computer simulations of the electron exchange between incident ion and surface atoms allow interpretation of the experimental data in terms of the quasi-resonant charge–exchange model. Highlights: Inelastic interaction of low energy Ar ions with zirconia surface was investigated experimentally. Intensity of scattered and sputtered ions depends non-monotonically on incident ion energy. Surface stoichiometry changes non-monotonically depending on the energy of ion irradiation. Quasi-resonant charge exchange between incident ion and surface was calculated by simulation. Simulation results of were compared with measurements and show good agreement.